Energy requirement for maintenance and growth of Bali cattle in East Timor - Yuliaty (Curtin University, 2013)
Low productivity of cattle in East Timor is a consequence of poor management and lack of nutritional knowledge. The study aimed at determining the energy and water requirements for Bali cattle for maintenance and growth using locally available feed resources. Maintenance energy requirements were estimated to be 0.40 -0.42 MJ/kg W0.75. Water requirement was similar to other cattle breeds, being 11.0+ 1.37 L/d.